2020
DOI: 10.1155/2020/5629717
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Molding Design and Optimization of the Molding Process Parameters of the Automobile Trunk Trim Panel

Abstract: In order to put forward the theoretical calculation formula for the compression force of the compression mold of the trunk trim panel, obtain the influence trend of the process parameters on the molding quality of the trunk trim panel, and obtain the optimal process parameters combination for the compression molding of the trunk trim panel, four process parameters, the heating temperature, time, compression pressure, and holding time, which affected the compression molding, were selected as the level factors; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…is article was to study the process of material compression molding and took out the part that involved heat separately for more comprehensive and in-depth research, so as to gain more experience and ideas [22].…”
Section: Discussionmentioning
confidence: 99%
“…is article was to study the process of material compression molding and took out the part that involved heat separately for more comprehensive and in-depth research, so as to gain more experience and ideas [22].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the sheet can be expanded to 2-3 times the thickness of the cold sheet. It should be indicated that the sheet temperature should be less than 230°C; otherwise, the PP polypropylene will degrade, thereby affecting the surface of the molded product and reducing the heat resistance and strength of the product [10,11]. e preheating time of the GMT sheet can be calculated through the following expression [12] (29):…”
Section: Sheet Warm-up Timementioning
confidence: 99%
“…Mold design on a hot press machine is an important factor affecting product quality, production efficiency, and costs. While heating temperature, heating time, compression pressure, and holding time are process parameters that need attention [20].…”
Section: Introductionmentioning
confidence: 99%